Pola Pertumbuhan dan Produksi ï¡-Amilase Bacillus amyloliquefaciens pada Substrat Pati Jagung dengan Variasi pH Awal Media dan Waktu Inkubasi - Wahyuningsih, Sisilia Sri; Mursyanti, Exsyupransia; Atmodjo, P. Kianto (Universitas Atma Jaya Yogyakarta, 2004)
The aims of this studyÂ were to identify the growth curve ofÂ B. amyloliquefaciens onÂ corn-starch and non corn starch addition media,Â number of cellsÂ and production of a-amylase on variety initial pH during the stationary phase. The growth curve of B. amyloliquefaciens was made using the water optical density on bothÂ medium which has inoculated by microbes. The experimental design for the a-amylase production was factorial completely randomized design (6 x 3 x 3). There were two factors included in this study i.e. initialÂ pH of the media ( 5,Â 5.5,Â 6,Â 6.5,Â 7 and 7.5) and incubation times (16, 18 and 20 hours). The results showed that B. amyloliquefaciens growth curve on medium with corn starch was slower than on medium without corn starch. Production ofÂ a-amylase and number of cells were having similar patterns in all treatments, i.e. increased until optimum pH and incubation time were reached. The number of cells and a-amylase production were optimal at pH 6.5 for 18 hours incubation whereas the number of cellsÂ (about 2.8542 x 108 cells/ml)Â and a-amylase production (1.4467 units/ml) were optimal at pH 6.5 for 18 hoursÂ incubation.